Pairs of amino acids at the P- and A-sites of the ribosome predictably and causally modulate translation-elongation rates. Issue 24 (4th December 2020) - Ahmed, Nabeel; Friedrich, Ulrike A.; Sormanni, Pietro; Ciryam, Prajwal; Altman, Naomi S.; Bukau, Bernd; Kramer, Günter; O'Brien, Edward P.
Graphical abstract: Highlights: Many molecular factors modulate translation rate of the codon at ribosome's A-site. Ribosome profiling reveals amino-acid identity at P-site affects translation speed. P-site amino acid mutation demonstrates predictable and causal influence on speed. Evolution has enriched fast-translating amino-acid pairs across proteome of yeast. Protein sequence has evolved to causally encode translation rate information. Abstract: Variation in translation-elongation kinetics along a transcript's coding sequence plays an important role in the maintenance of cellular protein homeostasis by regulating co-translational protein folding, localization, and maturation. Translation-elongation speed is influenced by molecular factors within mRNA and protein sequences. For example, the presence of proline in the ribosome's P- or A-site slows down translation, but the effect of other pairs of amino acids, in the context of all 400 possible pairs, has not been characterized. Here, we study Saccharomyces cerevisiae using a combination of bioinformatics, mutational experiments, and evolutionary analyses, and show that many different pairs of amino acids and their associated tRNA molecules predictably and causally encode translation rate information when these pairs are present in the A- and P-sites of the ribosome independent of other factors known to influence translation speed including mRNA structure, wobble base pairing, tripeptide motifs, positively charged upstream nascent chain residues, and cognate tRNA concentration. The fast-translating pairs of amino acids that we identify are enriched four-fold relative to the slow-translating pairs across Saccharomyces cerevisiae 's proteome, while the slow-translating pairs are enriched downstream of domain boundaries. Thus, the chemical identity of amino acid pairs contributes to variability in translation rates, elongation kinetics are causally encoded in the primary structure of proteins, and signatures of evolutionary selection indicate their potential role in co-translational processes.